INHIBITION OF TROPOMYOSIN-RECEPTOR-KINASE B AND PHOSPHOINOSITIDE 3-KINASE/PROTEIN KINASE B SIGNALING CASCADE - Yen, Tran Phi Hoang (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2014)
Trimethyltin (TMT, 2.4mg/kg, i.p) can trigger neuronal damage by inhibiting Tropomyosin receptor kinase B (TrkB receptor) following by phosphoinositide 3-kinase (PI3K)/protein kinase B or Akt signaling cascade. We examined hippocampal changes in TrkA/B phosphorylation on Tyr490/Tyr516 of TMT-treated mice in a time-dependent manner. Phosphorylated PI3K (Tyr508), phosphorylated 3-phosphoinositide-dependent protein kinase 1 (PDK1, Ser241) and phosphorylated Akt (Ser473) were changed following by TMT injury (from 3 hours until 7 days after injury). Treatment with 7,8-dihydroxyflavone (7,8-DHF), a specific agonist of TrkB, significantly attenuated the TMT-caused inhibition of phospho-TrkB, thereby increased in expressions of phospho-PI3K, phospho-PDK1 and phospho-Akt in TMT-treated mice, simultaneously 7,8-DHF showed a neuroprotective effect in observation of nuclear chromatic clumping by Cresyl violet- and terminal deoxynucleotidyltransferase-mediated dUTP-biotin nick end labeling- (TUNEL) staining in the hippocampal dentate gyrus (DG) of TMT-treated mice, as compared to saline-treated group. This finding suggests that inhibition of TrkB receptor following by PI3K/Akt cascade may play a part in the molecular mechanism by which TMT caused neurodegeneration in mice.